The Soft Power of Framing: Constructing Istanbul as a Regional Art Centre - Jérémie Molho (European Journal of Turkish Studies)
In the last ten years, ties between the art worlds of Istanbul and its surrounding region have been increased. These developments would initially appear to be a component of so-called “Turkish soft power”, indicating the rise of Turkey’s regional influence. Through the analysis of organisational dynamics in the case study of Istanbul, this paper critically questions the representation of the arts sector as an instrument of state or corporate interests. Rather than being dependent on hard factors alone, the geography of the global art market results from the social construction of space. This paper analyses discourses on the Middle East as an emerging art market and on the rise of new cities as regional art centres as the production of cognitive frames. Local art actors have emphasised the cultural proximity of Turkey to the region and the mutually shared interest of challenging Western hegemony in the international art world. Thereby, they have framed Istanbul as an emerging regional art centre.